Los memes, un producto comunicacional de visibilización y construcción de imaginarios políticos en Ecuador (Monográfico) - Celorio Moreno, Gabriela Alexandra (2020)
The memes are communicational products that proliferate in social networks and are received by thousands of people, they are identified by their entertaining content and with innocent content, however, these devices have a lot of reception when there is a political event as in this case the Referendum 2018 in Ecuador. This research paper tries to identify how the memes help the construction of new political imaginary and how they visualize imaginary that are established in Ecuadorian society, will also focus on identifying what are the social imaginary built and visualized in two of the most visited pages in Ecuador that are Crudo Ecuador and Soy Revolución, from a specific political issue that is the Referendum 2018.